Time's arrow, time's cycle: Granulite metamorphism and geodynamics. (12th April 2019) - Brown, Michael; Johnson, Tim
Abstract: Although the thermal evolution of the mantle before c. 3.0 Ga remains unclear, since c. 3.0 Ga secular cooling has dominated over heat production—this is time's arrow. By contrast, the thermal history of the crust, which is preserved in the record of metamorphism, is more complex. Heat to drive metamorphism is generated by radioactive decay and viscous dissipation, and is augmented by the influx of heat from the mantle. Notwithstanding that reliable data are sparse before the Neoarchean, we use a dataset of temperature ( T ), pressure ( P ) and thermobaric ratio ( T / P at the metamorphic 'peak'), and age of metamorphism ( t, the timing of the metamorphic 'peak') for rocks from 564 localities ranging in age from the Cenozoic to the Eoarchean eras to interrogate the crustal record of metamorphism as a proxy for the heat budget of the crust through time. On the basis of T / P, metamorphic rocks are classified into three natural groups: high T/P type ( T/P >775°C/GPa, mean T/P 1105°C/GPa), including common and ultrahigh-temperature granulites, intermediate T/P type ( T/P between 775 and 375°C/GPa, mean T/P 575°C/GPa), including high-pressure granulites and medium- and high-temperature eclogites, and low T/P type ( T/P <375°C/GPa, mean T/P 255°C/GPa), including blueschists, low-temperature eclogites and ultrahigh-pressure metamorphic rocks. A monotonic increase in the P of intermediate T/P metamorphism from the Neoarchean to the Neoproterozoic reflects strengthening of the lithosphere during secular cooling of the mantle—this is also time's arrow. However, temporal variation in the P of intermediate T/P metamorphism and in the moving means of T and T / P of high T/P metamorphism, combined with the clustered age distribution, demonstrate the cyclicity of collisional orogenesis and cyclic variations in the heat budget of the crust superimposed on secular cooling since c. 3.0 Ga—this is time's cycle. A first cycle began with the widespread appearance/survival of intermediate T/P and high T/P metamorphism in the Neoarchean rock record coeval with amalgamation of dispersed blocks of lithosphere to form protocontinents. This cycle was terminated by the fragmentation of the protocontinents into cratons in the early Paleoproterozoic, which signalled the start of a new cycle. The second cycle continued with the progressive amalgamation of the cratons into the supercontinent Columbia and extended until the breakup of the supercontinent Rodinia in the Neoproterozoic. This cycle represented a period of relative tectonic and environmental stability, and perhaps reduced subduction during at least part of the cycle. During most of the Proterozoic the moving means for both T and T / P of high T/P metamorphism exceeded the arithmetic means, reflecting insulation of the mantle beneath the quasi-integrated lithosphere of Columbia and, after a limited reorganisation, Rodinia. The third cycle began with the steep decline in thermobaric ratios of high T/P metamorphism to their lowest value, synchronous with the breakup of Rodinia and the formation of Pannotia, and the widespread appearance/preservation of low T/P metamorphism in the rock record. The thermobaric ratios for high T/P metamorphism rise to another peak associated with the Pan-African event, again reflecting insulation of the mantle. The subsequent steep decline in thermobaric ratios of high T/P metamorphism associated with the breakup of Pangea at c. 0.175 Ga may indicate the start of a fourth cycle. The limited occurrence of high and intermediate T/P metamorphism before the Neoarchean suggests either that suitable tectonic environments to generate these types of metamorphism were not widely available before then or that the rate of survival was low. We interpret the first cycle to record stabilisation of subduction and the emergence of a network of plate boundaries in a plate tectonics regime once the balance between heat production and heat loss changed in favour of secular cooling, possibly as early as c. 3.0 Ga in some areas. This is inferred to have been a globally linked system by the early Paleoproterozoic, but whether it remained continuous to the present is unclear. The second cycle was characterised by stability from the formation of Columbia to the breakup of Rodinia, generating higher than average T and T / P of high T/P metamorphism. The third cycle reflects colder collisional orogenesis and deep subduction of the continental crust, features that are characteristic of modern plate tectonics, which became possible once the average temperature of the asthenospheric mantle had declined to <100°C warmer than the present day after c. 1.0 Ga.